A study on the machining parameters optimization of WEDW machining TI-6AL-4V: effect on surface roughness, MRR and cutting speed - Ahmad Fairuz, Mansor (Universiti Malaysia Perlis, 2008)
The purpose of this project is to optimize the WEDM combination parameters in order to get the highest material removal rate (MRR), fastest cutting speed (CS) and finest surface roughness (SR) on material of titanium alloy (Ti6Al4V). This project begins with a preliminary design that proposes on the design factors which have possibility to affect the responses. This step is done with the review on the literatures and getting some experience from the technical users. After that, experiments are come out to select the suitable parameters. Eight (8) parameters are selected including electrolysis free (EF), intensity peak current (IP), time on (ON), time off (OFF), flushing rate (FR), voltage (V), wire speed (WS) and flushing pressure (WP). All parameters’ values are adjusted and applied on the panel except the flushing rate (FR) on the valve. It starts with application of Design of Experiment (DOE) on Taguchi Method that applying L-18 (21,37) from the Orthogonal Array (OA). Results which have been obtained from the 18 trials of experiments are analyzed to get the optimum condition and predicted value. Also an analysis is done on multi-responses by software to get a best combination factors for all combination of the responses. The last stage is confirmation test to see the percentage of error comparing with the actual value. All results have been discussed.